2013
DOI: 10.1016/j.jtcvs.2013.07.065
|View full text |Cite
|
Sign up to set email alerts
|

Impact of varying degrees of renal dysfunction on transcatheter and surgical aortic valve replacement

Abstract: Worsening renal function was associated with increased in-hospital mortality, hospital length of stay, and ICU length of stay in SAVR patients, but not in TAVR patients. This unexpected finding may have important clinical implications in patients with aortic stenosis and preoperative renal dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 18 publications
5
55
1
Order By: Relevance
“…[10][11][12][13][17][18][19][20][21] The characteristics of the included studies are reported in Table 1. There was no significant variability in the CKD definitions used across the studies.…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12][13][17][18][19][20][21] The characteristics of the included studies are reported in Table 1. There was no significant variability in the CKD definitions used across the studies.…”
Section: Resultsmentioning
confidence: 99%
“…TAVR has been shown to be at least as safe and effective as SAVR in patients with CKD and CLD. [15][16][17][18] However, patients with CKD and CLD undergoing TAVR are at increased risk of procedural complications, mortality, and rehospitalization when compared with those without these conditions. 17,18 In addition to patient comorbidities, TA-TAVR and AKI were also identified as independent predictors of 30-day readmission.…”
Section: Discussionmentioning
confidence: 99%
“…Data on renal function before SAVR are extensive but have been examined in less detail, with some studies showing decreased survival with advanced CKD9 17 and others suggesting renal function has little effect on mortality 7 18. However, a recent systematic review has highlighted that both in-hospital and longer term mortality is very high among dialysis patients undergoing any type of surgical valve replacement 19.…”
Section: Discussionmentioning
confidence: 99%
“…Large scale outcome data examining the impact of CKD on outcomes after TAVI are still lacking and studies to date have been inconsistent. While some studies have found a relationship between renal dysfunction and worse outcomes,8 others have not 9 10. A recent study demonstrated that although advanced CKD was an independent risk factor for mortality, earlier stage disease was not.…”
Section: Introductionmentioning
confidence: 99%